Evaluation of usability and user feedback to guide telepharmacy application development in Indonesia: a mixed-methods study - Alfian, Sofa D; Sania, Jihan A; Aini, Dzulfah Q; Khoiry, Qisty A; Griselda, Meliana; Ausi, Yudisia; Zakiyah, Neily; Puspitasari, Irma M; Suwantika, Auliya A; Mahfud, Mariska; Aji, Saktian; Abdulah, Rizky; et al. (My University, 2024)
In Indonesia, the adoption of telepharmacy was propelled by the COVID-19 pandemic, prompting the need for a user-friendly application to support both the general population and pharmacists in accessing healthcare services. Therefore, this study aimed to evaluate usability and user feedback of a pioneering telepharmacy application known as Tanya Obat (translating to "Ask about Medications") in Indonesia, from the perspectives of the general population and pharmacists. A mixed-methods sequential study was conducted with the early-stage Tanya Obat application in Bandung City. Participants, including the general population and pharmacists, were instructed to use the application for a week. Questionnaires for the general population and pharmacists were distributed from March to May and February to June 2023, respectively. The System Usability Scale questionnaire was adopted to describe usability of the developed application. Further exploration of the quantitative results required collecting open-ended feedback to assess the impressions of the participants, difficulties encountered, and desired features for enhanced user-friendliness. The collected statements were summarized and clustered using thematic analysis. Subsequently, the association between the characteristics of participants and perceived usability was determined with the Chi-square test. A total of 176 participants, comprising 100 individuals from the general population and 76 pharmacists, engaged in this study. In terms of usability, the questionnaire showed that Tanya Obat application was on the borderline of acceptability, with mean scores of 63.4 and 64.1 from the general population and pharmacists, respectively. Additionally, open-ended feedback targeted at achieving a more compelling user experience was categorized into two themes, including concerns regarding the functionality of certain features and recommendations for improved visual aesthetics and bug fixes. No significant associations were observed between the characteristics of participants and perceived usability (p-value > 0.05). The results showed that the perceived usability of Tanya Obat developed for telepharmacy was below average. Therefore, feature optimizations should be performed to facilitate usability of this application in Indonesia.
Keywords: Indonesia; Mobile application; Telemedicine; User-centered design